Production and Purification of Water from Humid Air by Using Activated Carbon Method - Gnanasekaran, R.; K, Ramya.; Yuvaraj, D.; Jamela, Noorul (International Journal of Engineering and Technology, 2018)
Drinking Water scarcity is one of the leading issue in our growing world. The atmospheric air contains large amount of water in the form of water vapor, fog, mist etc.In which 30% of water is wasted.Under this situation the climatic conditions of many regions are suitable for generating water. This moisture content is processed by condensation principle to produce fresh water that may be used as distilled water in laboratory and further purification leads to drinking water purity level. Here cooling is produced by Peltier effect and hot air is passed to cooling medium and when it reaches dew point it start condensing water from air. The obtained water from air contain excess of contaminants such as bacteria, nitrate, nitrate, odor, ammonium etc.., these toxic substances are remove by using biofiltration method. In this research filter medium is constructed by extraction of Activated charcoal from coconut waste. . The main aim of our project is utilization of renewable resources that are already available in nature and turn back this energy into water. This project is design a device that can convert humid air directly into clean water.Â Â  Â